Cognition and freezing of gait in Parkinson's disease: A systematic review and meta-analysis. (April 2023) - Monaghan, A.S.; Gordon, E.; Graham, L.; Hughes, E.; Peterson, D.S.; Morris, R.
Abstract: Freezing of gait (FOG) is a common and disabling symptom in people with Parkinson's Disease (PwPD). Although cognition is thought to be worse in PwPD who freeze, a comprehensive analysis of this relationship will inform future research and clinical care. This systematic review and meta-analysis compared cognition between PwPD who do and do not exhibit FOG across a range of cognitive domains and assessed the impact of disease severity and medication status on this relationship. 145 papers (n = 9010 participants) were included in the analysis, with 144 and 138 articles meeting the criteria to assess moderating effects of disease severity and medication status, respectively. PwPD who freeze exhibited worse cognition than PwPD without FOG across global cognition, executive function/attention, language, memory, and visuospatial domains. Greater disease severity and "ON" levodopa medication status moderated the FOG status-cognition relationship in global cognitive performance but not in other cognitive domains. This meta-analysis confirmed that cognition is worse in PwPD with FOG and highlights the importance of disease severity and medication status in this relationship.